Chile : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report ;, 2007)
This Report on the Observance of Standards and Codes data module provides an assessment of Chile's macroeconomic statistics against the Special Data Dissemination Standard (SDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that Chile's macroeconomic statistics are timely, generally of high quality, and adequate to conduct effective surveillance. There is a high degree of quality awareness among Chile's statistical managers and a reputation of integrity of the statistical institutions and processes among data users. However, there is scope for improvement in some areas.